The Correlation Of 1 Month Injection Hormonal Contraception With Cognitive Function Of Acceptor In Tanjung Rema Public Health Center Martapura Sub-District Banjar Regency - Luckyta Ibna Permana; Nurul Hidayah (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Among all of acceptor in Martapura sub-district, 91.8% use hormonal contraception. Injection contraception is the most acceptor choose to use, that is bout 55.8%. This contraception is including estrogen and progesterone hormone. Estrogen hormone is really important as long a woman life, beside for sexual function and reproductive, itâ€™s also important to decline the decreasing of cognitive function.Purpose: The aim of this research is to know the correlation between 1 month injection hormonal contraception with cognitive function of acceptor in Tanjung Rema Public Health Center Martapura sub-district Banjar regency.Method: The method used analytic with cross sectional. The subject is hormonal acceptors and collected by purposive sampling.Result: Respondents who used 1 moth injection of hormonal contraception bout 67.6% and non 1 moth injection contraception was bout 32.4%. The total of respondents who has dementia cognitive function was 2.9%, â€œborderlineâ€ dementia was 14.7%, moderate cognitive function was 29.4%, and good cognitive function was 52.9%. Based on statistic test use chi-square test, that was p = 0.008 or less than Î± = 0.05.Conclusion: Concluded there has significant relation between 1 month injection hormonal contraception with acceptor cognitive function. Suggested that this results can be use for promotion program. Which beside as contraception it can uses as cognitive function defender.Â Keywords: 1 month injection, acceptors, cognitive function, contraception